THE RELATIONSHIP OF PREGNANT WOMEN WITH CHRONIC LACK OF ENERGY AND THE INCIDENT OF LOW BIRTH WEIGHT BABIE - Prameswari, Veryudha Eka; Frilasari, Heni (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Low Birth Weight is the cause of infant death in East Java. This is influenced by chronic energy deficiency which results in babies being born prematurely. The research aims to determine the relationship between chronic energy deficiency in pregnant women and the incidence of Low Birth Weight. The analytical research design uses a Retrospective Cohort using 53 samples calculated by the Slovin formula and total sampling in the technique. The data analysis used was univariate and bivariate chi-square. Getting results from 16 respondents who experienced BBLR as much as 30.2%, as many as 20 respondents who were pregnant women experienced KEK 37.7%. Based on analysis tests, it was found that half of pregnant women with KEK had a Low Birth Weight of 50.0%. Meanwhile, the results of the bivariate analysis with Chi-square obtained a p-value of 0.014 where p < α 0.05, which states that there is a relationship between KEK pregnant women and the incidence of Low Birth Weight in PMB Cemandi. The OR value is 4.5 which states that pregnant women with CED have a 4.5 times risk of having a Low Birth Weight baby